2013
DOI: 10.14742/ajet.65
|View full text |Cite
|
Sign up to set email alerts
|

Investigating elementary school students' technology acceptance by applying digital game-based learning to environmental education

Abstract: <p class="Abstract">In order to improve and promote students' environmental knowledge, attitudes, and behaviour, integrating environmental education into the primary education curriculum has become a key issue for environmental education. For this reason, this study aimed to investigate elementary school students' acceptance of technology applying digital game-based learning (DGBL) to environmental education. A total of 32 fourth graders in an elementary school participated in a seven-week DGBL teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 51 publications
5
45
0
13
Order By: Relevance
“…Hence, a student's positive attitude towards using WebCT could encourage him/her to pursue more resources; while this positive attitude also helps the student to believe WebCT is useful. Cheng, Lou, Kuo, and Shih (2013) examined students' acceptance of technology in digital game-based learning by measuring students' EOU, U, and user intentions through a survey. Results of the path analysis model were similar to those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a student's positive attitude towards using WebCT could encourage him/her to pursue more resources; while this positive attitude also helps the student to believe WebCT is useful. Cheng, Lou, Kuo, and Shih (2013) examined students' acceptance of technology in digital game-based learning by measuring students' EOU, U, and user intentions through a survey. Results of the path analysis model were similar to those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, maximising a game's verisimilitude can be part of the game-master's quest. Cheng et al (2013) interviewed 32 students who had undertaken a new approach using digital game-based learning, deriving from the board game Monopoly. They found that respondents considered the approach highly motivating, particularly compared to the unspecified previous approaches they had undertaken.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%
“…Al mismo tiempo los instrumentos de diagnóstico utilizados se han presentado fiables, mostrando índices de fiabilidad similares a los alcanzados por otros autores en diferentes investigación, y ello ocurría tanto con el instrumento IMMS (Huang, Huang, & Tschopp, 2010;Keller, 2010;Che, 2012;Di Serio, Blanca, & Delgado, 2013;Yufeng & Yamanaka, 2013;Proske, Roscoe, & McNamara, 2014) como con el TAM (Yong, Rivas, & Chaparro, 2010;Park, Nam, & Cha, 2012;Ho, Hung, & Chen, 2013;Cheng, Lou, Kuo, & Shih, 2013;Tarhini, Hone, & Liu, 2014).  Los objetos de aprendizaje en RA se presentan como materiales educativos de utilidad para el aprendizaje de los alumnos de Medicina, aspecto en el que coincidimos con otros autores (Yeo et al, 2011;Wu, Wen-Yu, Chang & Liang, 2013;Bower et al, 2014).…”
Section: Secuenciaunclassified